Certification - Melodye Lehnerer (Clinical Sociology Review)
The application of sociological knowledge, including theory, methods, and skills, has been identified as sociological practice.  Within the field of sociological practice there are two distinct types of practice - clinical and applied (Clark and Fritz 1986).  In the United States (U.S.) the Association for Applied and Clinical Sociology (AACS) certifies these sociological practitioners at the master’s or doctoral level. The process involves an evaluation by previously certified peers and includes the submission of a portfolio and the completion of a demonstration in which applicants showcase their action-oriented work. Certification is not state licensure. The credentialing of sociological practitioners in the U.S. and internationally can serve as a model for sociological practitioners globally - applied, clinical, and engaged public.